Special Simplex Algorithm for Linked Problems - Heesterman, A. R. G.; Sandee, J. (Management Science, 1965)
This paper describes a variant of the Simplex algorithm, applicable to matrices containing blocks of elements along and just below the diagonal. It uses the emptiness of the other blocks to save space and computation.